Rapid conversion of IgG to biosensor using an antibody-binding protein-based probe. Issue 20 (10th September 2021) - Zhao, Guangwei; Li, Haimei; Li, Baowei; Li, Mei; Xu, Wei; Chen, Limei; Wang, Baoqiang; Dong, Jinhua
Abstract : A fluorescent probe that can quickly convert full-length antibodies to Quenchbodies was successfully developed. Abstract : We successfully developed a fluorescent probe that can quickly convert full-length antibodies to Quenchbodies, which represent a type of fluorescent immunosensor with high binding affinity and specificity depending on the reaction of antigens and antibodies. An anti-testosterone IgG was successfully converted to an immunosensor that detects testosterone with a limit of detection (LOD) of 0.76 nM and concentration for 50% of maximal effect (EC50 ) of 61.5 nM. Another IgG-based immunosensor detected ractopamine with an LOD of 15.5 pM and EC50 of 48.6 nM.